E-Wallet Attractiveness among Generation Z during the COVID-19 Pandemic - Andrew Christian Aseng; Lanemey Brigitha Pandeirot (CogITo Smart Journal, 2023)
The COVID-19 pandemic has made people start to move to non-cash transactions. This study aimed to find out the attractiveness of e-wallet for gen Z during this pandemic. The research questionnaire was constructed based on literature reviews, previous research as well as in-depth interview with several people from gen Z. After the validity and reliability tests were carried out, the final questionnaire containing 34 question items was distributed to 328 respondents online using convenience and snowball sampling methods. Factor analysis technique was carried out and obtained five factors that make e-wallet attractive according to gen Z: functionality, reputation, accessibility, promotion, and money management.